Review of Pavement Thickness and Road Damage Using an Empirical Approach - Lakawa, Irwan; Syamsuddin, Syamsuddin; Hujiyanto, Hujiyanto; Alfian, Muhammad Fikri (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
Road damage can be attributed to several factors, including high traffic volume, excessive vehicle loads, subgrade bearing capacity, and climatic conditions. Common. methods for road pavement planning include the Road Note 31 method, AASHTO 1993, Component Analysis, and the 2017 Pavement Design Manual. This study aims to review pavement thickness and identify the damage levels on the Palingi-Lansilowo road in Konawe Islands Regency. The analysis results indicate that 50% of the road pavement falls into the Severely Damaged category, while the remaining 50% is classified as Moderately Damaged. The dominant causes of road damage are climatic factors and subgrade bearing capacity. The pavement thickness determined using the Component Analysis method includes subbase course of Class C Sand and Gravel (15 cm), base course of Class C Crushed Stone (15 cm), and surface course of Asphalt Concrete (5 cm). This review is based on traffic survey results from 2023. Therefore, it is recommended to reassess the road condition and pavement thickness in the next 10 years, considering urban development and traffic growth rate.